2017
DOI: 10.1093/geront/gnx082
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functioning Among Older Adults New to Long-Term Services and Supports

Abstract: Diverse health, activity, and environmental factors may facilitate early identification of new LTSS recipients most in need of interventions to optimize self-reported PF. Several health conditions may be targets for such interventions. Additional research is needed to evaluate and compare PF trajectories among older adults receiving LTSS in diverse settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…7 A North American study indicated that monitoring physical functioning based on health, activity, and environmental factors may facilitate early identification of future long-term care and social support needs. 8 Handgrip strength might be an indicator of poor physical functioning since older adults with sarcopenia (decreased muscle mass) have poor physical functioning. 9 The 4-m timed walk test is a simple, low-cost, and rapid tool that can be a good marker of decline in physical functioning in community-dwelling older adults.…”
Section: Research Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A North American study indicated that monitoring physical functioning based on health, activity, and environmental factors may facilitate early identification of future long-term care and social support needs. 8 Handgrip strength might be an indicator of poor physical functioning since older adults with sarcopenia (decreased muscle mass) have poor physical functioning. 9 The 4-m timed walk test is a simple, low-cost, and rapid tool that can be a good marker of decline in physical functioning in community-dwelling older adults.…”
Section: Research Reportmentioning
confidence: 99%
“…Literature shows physical functioning measured by walking speed as an individual predictor of hospitalization in older adults with and without multimorbidity 7. A North American study indicated that monitoring physical functioning based on health, activity, and environmental factors may facilitate early identification of future long-term care and social support needs 8…”
Section: Introductionmentioning
confidence: 99%
“…In congruence with this, a study in the United States revealed significant associations between diverse social and health-related activities and elders' independence in IADLs. [39] On the same line, the rates of independence in IADLs tend to be high in developed countries such as in Norway where Boulos et al [25] reported that 61.7% of the elderly were fully independent. Conversely, the rates are low in developing countries such as in Turkey, [29] where the rate was 25.3%, close to the rates in the present study.…”
Section: Discussionmentioning
confidence: 96%